2020
DOI: 10.1590/1413-785220202802225507
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Quality of Life and Radiological Parameters After Hallux Valgus Correction

Abstract: Objective: To evaluate the correlation between postoperative quality of life and the severity of hallux valgus deformity. Methods: A total of 23 patients underwent moderate (n = 14) and severe (n = 9) hallux valgus (HV) surgical correction with the Scarf technique between January 2010 and December 2012. The mean follow-up time was 60 months. Participants answered the SF-36 quality of life assessment questionnaire and their radiographs were evaluated at three different moments (preoperative, 1 and 5 years af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…This has a direct correlation with and could be the best predictor of good results (16)(17)(18) . The severity of the deformity or the correction of radiographic measurements (HVA/IMA), alone, does not necessarily have a direct correlation with an improvement in functional scores (6,19) . Axt et al (20) reported a 90% satisfaction among patients after Keller-Brandes operation for hallux valgus, despite 23% of the feet remaining with an altered HVA of more than 30 degrees (20) .…”
Section: Discussionmentioning
confidence: 99%
“…This has a direct correlation with and could be the best predictor of good results (16)(17)(18) . The severity of the deformity or the correction of radiographic measurements (HVA/IMA), alone, does not necessarily have a direct correlation with an improvement in functional scores (6,19) . Axt et al (20) reported a 90% satisfaction among patients after Keller-Brandes operation for hallux valgus, despite 23% of the feet remaining with an altered HVA of more than 30 degrees (20) .…”
Section: Discussionmentioning
confidence: 99%